PELATIHAN PEMBUATAN PETA KONTUR TIGA DIMENSI DENGAN MENGGUNAKAN PROGRAM SURFER - Noya, Yunita A.; Loupatty, Sven R.; Manuputty, Gratia D.; Ratuluhain, Eva Susan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
Knowledge and skills about making three-dimensional contour maps are essential and promising to be mastered by a Marine Science graduate as a provision of knowledge that can be applied to work life, which is not only to fisheries and maritime affairs but also to other fields that require geographic information systems, such as agriculture. One of the most widely applied programs for making three-dimensional contour maps is Surfer. However, sometimes the knowledge and skills acquired in college are not profound, hence, training is carried out using the program to improve the skills of alumni. The activity was carried out for 2 days. The training begins with identifying participants' basic knowledge of the Surfer program. Based on the initial identification, it was found that the participants' basic knowledge varied widely and the average was still below 50%. Next is an introduction to the Surfer program, including the available menus and the functions of these menus. During the introduction of theory, participants were trained in their skills simultaneously using a laptop display, where this method was effective for participants because it was directly practised. After that, the participants were tested again for their abilities related to mastery of knowledge and skills. The results of the training showed an increase in the knowledge and skills of the participants who were capable of making 3D contour maps using the Surfer program.